Designing sustainable large-scale industrial plantation landscapes: use of natural forest remnants and corridors to maintain biodiversity, retain environmental functions/services, and reduce social tensions between plantation companies and local people - Poulsen, J. (Sangju National University, Department of Forest Resources, 2001)
Tropical large-scale industrial plantations are rapidly expanding as a source of industrial wood and fuel and are also often used as part of afforestation and reforestation schemes. The article explores how appropriate design and management of natural forest corridors and remnant patches may be used to mitigate or reduce the negative impacts of large-scale industrial plantations on native biodiversity and towards maintenance of environmental and social functions of the original natural forest landscape. First, plantation landscapes should be designed so that the landscapes are penetrable and permeable for those biodiversity components which are of conservation concern in the area under consideration, but impenetrable and impermeable for pests, weeds, and invasive. Second, from a human/social standpoint, the priority must be to design plantation and manage landscapes in a way that minimizes the adverse impacts on the local people and communities living in and around these areas. This paper presents work conducted in Riau, Sumatra, Indonesia. Incentives for better landscape/spatial design and management of those areas that are set aside from production for corridors and conservation areas are identified. Corridors have been considered as merely constraints to maximizing short-term earnings. Potential short-term economic incentives and benefits include: minimizing plantation damage caused by wind throw, fire and insect pest attack (by functioning as windbreaks, firebreaks, and providing habitat for biological control organisms), protecting and maintaining water quality and supply to both the plantation stands and the people living there, providing resources such as beneficial plants, and other NTFPs, for those local people who live within and around the plantation landscape, and, decreasing the plantation establishment and maintenance cost. The paper also describes improved sets of criteria and indicators for sustainable management of large-scale plantations, by i) suggesting increasing emphasis on landscape scale and conservation and socio-economic issues, and, ii) ensuring that the criteria and indicators are sufficiently linked to practical management, specifically by establishing explicit links between the criteria and indicator sets and codes of practice.